THE POSITION OF CREDIT LINKED NOTES IN THE SYSTEM OF FINANCIAL MARKET INSTRUMENTS AND SECURITIES AND FEATURES OF THE REGULATION NOTES OPERATIONS - Olesya A. Yuzhakova (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article looks into the credit linked notes. Credit linked notes related to derivative financial instruments of the second generation or as they often refer to credit derivatives appeared after the appearance of the traditional financial derivatives such as swap contract, forward contract, futures contract. And if, from a legal point of view, credit derivatives are contract, from the economic point of view, this is a financial tool that allows to redistribute the cash flows between the participants of transactions with credit derivative. The combination of features of traditional securities and credit derivatives in the structure of credit notes, determines the complexity of the legal regulation and economic determination the place of credit notes in the structure of the financial instruments of the securities market.